Essay on secular stagnation - Lancastre, Manuel Corrêa de Barros de (2015)
In this paper we show that a closed economy, with a balanced budget and unable to increase public spending, can avoid or leave a persistent slump through adequate and timely combination of monetary and fiscal policy based on distortionary taxation. We use a three generations OLG New Keynesian model in which a permanent slump is possible without any self-correcting force to full-employment. Complementing recent work on Secular Stagnation using lump-sum taxation and government spending as fiscal instruments, our contribution is to use distortionary taxes over labor, consumption and capital, in a balanced budget environment with constant (or decreasing) government spending.